Further Study into Obstructive Jaundice and Ischaemic Renal Damage. Issue 5651 (26th April 1969) - Baum, M.; Stirling, G. A.; Dawson, J. L.
Abstract : Renal ischaemia for one hour in two groups of Gunn rats, one with and the other without bile-duct ligation, produced comparable reversible renal tubular lesions in both groups. Since Gunn rats have an unconjugated hyperbilirubinaemia, which is unaffected by bile-duct ligation, it seems likely that the high levels of bilirubin glucuronide are responsible for sensitizing the renal tubules to ischaemia, possibly by depressing cell respiration.